Design Elements, Form & Space: A Graphic Style Manual for Understanding Structure and Design - Puhalla, Dennis M. (Beverly, Mass Rockport, 2011)
Design principles never change. They serve as the foundation of the designer's thought process and are the essential tools that define a visual language. With hundreds of fundamental principles for creating successful design compositions, Design Elements: Form & Space establishes a basis for visual organization strategies and serves as a comprehensive manual for graphic designers. Understanding how elements interact in a layout is a critical step in stimulating visual thinking and compositional decision-making, and this book illustrates these principles in numerous diagrams, drawings, and practical examples of application. You'll also learn how conventional color harmonies effect form and space and how to apply elements to images and type to create balanced layouts. Gain a deeper aesthetic understanding of form in the context of ordering space with Design Elements: Form & Space.
Includes Index
Keywords: Composition (Art)